1985
DOI: 10.1111/j.1464-410x.1985.tb07034.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoscopic Treatment after Radical Radiotherapy for Invasive Bladder Cancer

Abstract: In a 6-year period 232 patients were treated by radical radiotherapy for transitional cell cancer of the bladder. Fifty-eight patients had secondary surgical management to control either locally persistent or recurrent tumour. Endoscopic treatment alone was used in 31 patients with down-staged tumours and the survival of this group compared favourably with that of 27 patients selected for salvage cystectomy (5-year survival rate 88% cf. 44%). A group of patients with favourable prognostic factors may be identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A selected group of patients from this series who were surgically managed after primary radiotherapy has recently been reported (Smith et al, 1985). Downstaging was also shown to be present in many who were managed endoscopically.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A selected group of patients from this series who were surgically managed after primary radiotherapy has recently been reported (Smith et al, 1985). Downstaging was also shown to be present in many who were managed endoscopically.…”
Section: Discussionmentioning
confidence: 92%
“…Factors influencing local tumour control after radiotherapy have been studied. A detailed comparison of secondary cys-tectomy and endoscopic treatment has been made to see whether the results claimed by the earlier review (Smith et al, 1985) can be substantiated.…”
mentioning
confidence: 99%
“…Although salvage cystectomy remains the standard treatment, it has appreciable mortality and morbidity (Crawford and Skinner, 1980;Bloom et af., 1982) and may not be appropriate in some patients who might have difficulty in managing a urostomy appliance. It has been shown that recurrent bladder cancer after radiotherapy can be managed reasonably successfully by endoscopic means (Smith et al, 1985). However, in only two of their patients was the recurrent tumour invading muscle, unlike this series when all recurrent tumours were invading muscle and most were deeply invasive.…”
Section: Discussionmentioning
confidence: 54%